Āryapañcaviṃśatisāhasrikā Prajñāpāramitā - Vajrācārya, Vijayarāja; Maitreyanātha ca. 4.Jh. (Bhoṭa-Bhāratīya granthamālā ..., 2006)
Buddhist canonical text; critical edition based on rare manuscripts; includes Abhisamayālaṅkāra, ascribed to Maitreyanātha